Impact of Student-Student Interaction Learning Model Faced with Case of Studying IPA on V-Class in the MIS Hayatul Islam Cinangka - Hermawan, Cecep Maman; Rosfiani, Okta; Haidir, Narulita Kinandhani; Aulia, Suci Syakila; Putra, Putra; Aprilliano, M. Ravito Atmajaya (PT. Riset Press International, 2024)
of the constraints affecting the learning outcomes of the IPA in students is the lack of variation of the learning model used, then students end up feeling bored and unenthusiastic so that their learning results are interrupted. The study aims to investigate the influence of the Student-Student Interaction (SSI) learning model on the learning outcomes of V-grade students on the IPA students' eyes, using the comparison of the STAD cooperative learning model. (Student Team Achievement Divisions). This research uses a quantitative approach to experimental design with a quasi-experimental design. The study was conducted with a sample of 61 students divided into two, namely 31 experimental classes using the Student-Student Interaction learning model and 30 control class using the STAD learning model (Studant Team Achievement Divisions) in the academic year 2019/2020 at MIS Hayatul Islamiyah. Based on the results of the study using the hypothesis test and nonparametric test Mann Whitney with a 95% confidence rate showed a Sig. (2-tailed) value of 0.044 which means 0.044 < 0.05 so it can be concluded that there is a significant difference to the learning outcome of IPA class V between classes using the learning model SSI (Student-student Interaction) and class using the cooperative learning model STAD type (Student Teams Achievement Divisions).